Judgment Doesn't Heal the Hurting - Kara Lasater (Educational Considerations, 2019)
Judgment interferes with the development of all relationships. For students and families who have experienced trauma, judgment can be particularly devastating as it may further damage the survivor’s already compromised sense of safety, trust, and belonging. As educators, we must develop non-judgmental attitudes toward students and families, yet sometimes our lack of self-awareness and problematic ideological positions lead us to judge. In this essay, I describe my personal journey with families and the ideological shift I experienced as I became more self-aware and attentive to others’ stories. It is my hope that my experiences will challenge other educators to engage in critical self-reflection, to bear witness to the stories of children and families who have experienced trauma, and to move beyond judgment.
Keywords: Judgment; family-school relationships; family-school partnerships; trauma; ideology